Relationship between Palatal Mucosa Properties and Pressure-pain Threshold in Young Dentulous and Elderly Edentulous Subjects - Takeuchi, Sawako; Isobe, Akio; Takamatsu, Naoya; Shimodaira, Osamu; Kotani, Yuko; Kitagawa, Noboru; Hara, Satoshi; Sato, Yuji; Tanaka, Satomi (Ronen Shika Igaku, 2015)
The present study aimed to clarify the relationship between the palatal mucosa properties and the pressure-pain threshold in both young dentulous and elderly edentulous subjects. The palatal mucosa in 17 elderly edentulous subjects (8 men,9 women；mean age：78.4 years) were measured at three points：the median point of the palate, the midpoint between the median point of the palate, and the lateral point of the first molar. Parameters of palatal mucosa were thickness (T [mm]) and modulus of elasticity (E [MPa]). Parameters of pressure-pain threshold were subsidence (S [mm]), pressure (P [MPa]), and compressibility [C [%]). A group of 17 young dentulous subjects was included as control. A Mann-Whitney U-test and a Spearmanʼs rank correlation coefficient were used to determine correlations between the thickness and the pressure-pain threshold at each measurement point. The greatest T and the smallest E, P, and C were found in elderly edentulous subjects. In elderly edentulous subjects, S at the median part and lateral part remained comparable. T was not significantly correlated with the parameters of pressure-pain threshold (S, P, or C) in the elderly edentulous. The palatal mucosa of elderly edentulous subjects is thick and has low elasticity, and is thus prone to deformation at small loads, which resulted in comparable amounts of subsidence between young dentulous and elderly edentulous subjects.